Exploring the repurposed role of solithromycin as an antivirulence agent against Staphylococcus aureus and its resistant variants - Alfaraj, Rihaf; Alkathiri, Fai A.; Alamri, Lama A.; Alnassar, Najd B.; Alanazi, Sarah H.; Algarni, Razan A.; Alhabdan, Norah S.; Abuthnain, Reema A. (Frontiers in Microbiology, 2025)
IntroductionStaphylococcus aureus is a bacterium that can cause various infections. The rise in Staphylococcal-resistant infections has led to the need for new treatments. The accessory gene regulator (agr) quorum-sensing system, which regulates the expression of genes involved in hemolysin, protease, and biofilm production, has been implicated in the virulence of S. aureus’s pathological characteristics.ObjectivesThis study investigates the potential of Solithromycin (SOL), a next-generation macrolide with broad-spectrum activity, to be repurposed as an antivirulence agent against S. aureus, MRSA, and ΔagrA strains.MethodsUsing various antibacterial assays, the antibacterial and antivirulence activities of SOL were evaluated against S. aureus, MRSA, and ΔagrA strains. The sub-inhibitory concentration MIC50 of SOL was tested for anti-virulence activity by assessing motility, biofilm formation, hemolysin, and protease production. Scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM) were used to visualize biofilm morphology. Conventional PCR was used to detect virulence genes following SOL treatment.ResultsSOL demonstrated significant antibacterial efficacy against S. aureus, MRSA, and ΔagrA strains with MIC90 (0.8 μg/mL) and MIC50 (0.4 μg/mL). SOL decreased S. aureus motility at MIC50 but had no effect on MRSA and ΔagrA strains. Hemolysin and protease activities were unaffected in all the tested strains. SEM and CLSM revealed significant reductions in biofilm formation and thickness. SOL at MIC90 and MIC50 reduced Congo red staining intensity. MIC50 inhibited MRSA and ΔagrA biofilms by 36.6 and 56.4%, respectively, with no significant effect on S. aureus biofilms in the crystal violet assay. PCR showed no leukocidin gene in the treated strains.DiscussionThis study highlights the potential of SOL as an antivirulence agent, emphasizing the importance of targeting regulators, such as ΔagrA, in managing S. aureus infections.